Step 1:
![\text{slope}=(y2-y1)/(x2-x1)=(-2-1)/(4-0)=-(3)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/h3x7y72nurf428nd9otuj8j65zyrpjxhr2.png)
Step 2: The equation is of the form y = mx + b, where m is the slope and b is the intercept, so we use the point (0,1) to find the y-intercept:
![\begin{gathered} y=mx+b \\ 1=-(3)/(4)(0)+b \\ b=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bkrai52iezkzz8037vk5vr4bceok50f26x.png)
y-intercept is 1
Step 3: The equation of the line in slope-intercept form is
![y=-(3)/(4)x+1](https://img.qammunity.org/2023/formulas/mathematics/high-school/nud1nm27hpc4fp84asj0xhtzgghy76psve.png)
Step 4: Graphing
for x = -4, y = 4
for x = 0, y = 1
for x =4, y = -2